Optimal extraction paths with electric power generation - Andreas A. Renz; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance, 2017)
It would seem that Hotelling's rule and its related models of resource extraction and electricity production as largest consumer of scarce resources are closely related. However, although fixed costs and a non-storable product are essential in characterizing electricity markets, they can hardly be found in respective literature. We show optimal extraction paths when coal, gas and a renewable with differing fixed and variable costs as well as carbon intensities are considered. The technology with lowest fixed costs will then - though relying on a scarce resource - always be used in perpetuity. The high fixed-cost fossil technology may be exploited at a definite point of time if it is relatively scarce or also used ad infinitum.
Keywords: C61; Q32; Q41; L94; 330; Scarce resoureces; Optimal control theory; Hotelling; Valuation; Non-renewable resource; Pollution target; Climate change; Peak-load-pricing